Teachers' Profile and Classroom Instruction Delivery: The Case of a Certain University in the Southern Philippines - Radjuni, Abubakar J. (HM Publisher, 2021)
Quality teachers are fundamental factor for offering quality education. This study's primary purpose was to determine the correlation between teachers' profiles and classroom instruction delivery. The descriptive-evaluative research design was used in the study. The study was conducted at the Mindanao State University- Sulu, College of Education. The study participants were composed of 10 faculty members and 100 students randomly selected from the college of education. The results revealed that the teachers always showed a mastery of the subject matter and teaching strategies. However, for interpersonal skills, they often exhibited it in the classroom. There was no significant relationship between teachers' profile and their competence in classroom instruction in terms of mastery of subject matter, teaching strategies, and interpersonal skills. Technology integration for teaching effectiveness is suggested for teachers to make them more effective in teaching. Interpersonal skills training is highly recommended for teachers every semester. The training will make them more effective in their interaction with students.